Survey Analysis of the Use, Effectiveness, and Patient‐Reported Tolerability of Inhaled Oxygen Compared With Injectable Sumatriptan for the Acute Treatment of Cluster Headache. Issue 10 (17th September 2018) - Schindler, Emmanuelle A.D.; Wright, Douglas A.; Weil, Marsha J.; Gottschalk, Christopher H.; Pittman, Brian P.; Sico, Jason J.
Abstract : Objective: In this secondary analysis of the Clusterbusters ® Medication Use survey, the use, effectiveness, and tolerability of inhaled oxygen were investigated and compared with injectable sumatriptan. We also sought to understand the predictors of medication response. Background: Inhaled oxygen is a mainstay abortive intervention in cluster headache but is not approved by the Food and Drug Administration (FDA). Unlike injectable sumatriptan, the only FDA‐approved pharmacologic intervention for cluster headache, oxygen can be used multiple times a day, which is highly relevant for a condition with numerous daily attacks. In addition to obstacles in obtaining oxygen therapy, optimal oxygen delivery (ie, mask, flow rate) is not uniformly employed in cluster headache. These factors lead to underuse and imprecise therapeutic response rates. Methods: A secondary analysis was conducted using deidentified data from the Clusterbusters ® Medication Use survey, which was modeled after previously published surveys and available online. Subjects were recruited from headache clinics and cluster headache websites. Most responses were chosen from a list; others were free‐texted. The final analysis included responses from 493 adult participants with a validated diagnosis of cluster headache. This analysis of deidentified data from the Clusterbusters ® Medication Use survey received institutional approval. Results: The most commonly used delivery system used by subjects was a non‐rebreather‐type mask. The use of oxygen flow rates >10 L/min was a positive predictor of medication response (OR = 2.36, P = .016). Among those who used flow rates >10 L/min, both inhaled oxygen (81.5%) and injectable sumatriptan (80.5%) were efficacious and did not differ significantly from each other in any specific group examined. At flow rates >10 L/min, positive predictors of oxygen response were male gender (OR = 2.07, P = .031) and cigarette smoking (current or historical; OR = 2.25, P = .017). Among the groups examined, there were no predictors of sumatriptan response. Most comments about side effects and concerns were directed at triptans. Conclusion: Therapeutic response to inhaled oxygen at sufficiently high flow rates (>10 L/min) had comparable efficacy to that of injectable sumatriptan for the acute treatment of cluster headache. Other factors in oxygen delivery (ie, flow rate changes) should be explored for optimization of therapy. The reasons for improved oxygen response in males and those with a cigarette smoking history require further exploration. While both oxygen and sumatriptan can be effective in the management of cluster headache, patient‐reported side effects and concerns were more commonly directed at triptan medications. Current restrictions on access to inhaled oxygen, which exist at many levels, limit the therapeutic options available for patients with cluster headache, thereby doing a disservice to this patient population and the providers who deliver their care.